2022-RA-295-ESGO Circulating cell free DNA and citrullinated histone H3 as useful biomarkers of NETosis in endometrial cancer. (20th October 2022) - Ronchetti, Livia; Terrenato, Irene; Ferretti, Margherita; Corrado, Giacomo; Goeman, Frauke; Donzelli, Sara; Mandoj, Chiara; Merola, Roberta; Zampa, Ashanti; Carosi, Mariantonia; Blandino, Giovanni; Conti, Laura; et al.
Abstract : Introduction/Background: Cancer mortality is mainly caused by organ failure and thrombotic events. NETosis, a chromatin release mechanism implemented by neutrophils, may contribute to these systemic effects. Our aim was to determine the occurrence of NETosis in endometrial cancer (EC) and analyzing tissue and serum NETosis biomarkers in EC patient to identify possible new targets for EC stratification and treatment. Methodology: Experiments were conducted on 63 EC patients (ranging from G1 to G3 grade) and 21 healthy controls (HC). Immunohistochemistry (IHC) and Immunofluorescence (IF) was performed on tumor tissue sections using antibodies against citrullinated histone H3 (citH3) (a marker of NETosis), neutrophil elastase (NE) and H2B. Serum levels of circulating free DNA (cfDNA), circulating free mitochondrial DNA (cfmtDNA) and citH3 were measured by qPCR using one microliter of deactivated serum, and by ELISA assay respectively. Fragmentation pattern of serum cfDNA was analyzed using the Agilent 2100 Bioanalyzer and High Sensitivity DNA Chips. Receiver operating characteristic (ROC) analysis was used to identify a cut off for cfDNA and cfmtDNA values able to discriminate EC from HC. Multiple correspondence analysis (MCA), between cfDNA, mtcfDNA, citH3 and blood parameters were used to identify associations among serum parameters in EC. Results: NETosis is activated in all EC grades. In EC sera, elevated cfDNA concentration is associated with citH3 in G1 and G2 EC. Categorizing by ROC cut off cfDNA and cfmtDNA value distributions, we observed that citH3 levels are significantly higher in samples with high values of cfDNA and low values of cfmtDNA A specific cfDNA fragmentation pattern characterizes EC and correlates with citH3 serum levels. Conclusion: NETosis could represent a new therapeutic target concerning EC. The combination of three serum parameters, citH3, cfDNA and cfmtDNA could be useful to monitor NETosis by non-invasive liquid biopsies opening the way for new therapeutic strategies in EC.